Social media as a language learning environment: a systematic review of the literature (2008-2019). Issue 9 (8th December 2022) - Barrot, Jessie S.
Abstract: This review maps the scientific literature on social media as a language learning environment published between 2008 and 2019. Over 1, 600 journals from the Scopus database were surveyed and 396 documents were analyzed using bibliometric analysis. The findings indicate that this field of interest has exponentially grown in the past 12 years and is likely to progress in the next several years. Although the scientific output is highly concentrated on the ten leading countries, the data also indicates its wide geographical distribution. As the first review to cover the 17 most popular social media platforms, the qualitative analysis of the findings of each study provided overwhelming evidence on the positive impact of social media as a language learning and teaching environment. The paper also reveals that high-profile platforms, such as Facebook, Skype, WhatsApp, and Twitter remain to attract the greatest attention from language learning scholars. This result was attributed to their multiple and flexible communication affordances, wide geographical distribution, and large number of active users. The paper concludes with implications for social media adoption and future studies.